A Case Study on Small Town Big Player – Enjay IT Solutions Ltd., Bhilad - Dr. Rajesh Kumar Pandey; Miss. Anjali D. Singh (International Journal of Engineering and Management Research, 2022)
Adequately trained Manpower is a problem that affects the IT industry as a whole, but it is particularly acute for Enjay IT Solution. Enjay's location in a semi-urban or rural area makes it even more difficult to find a talented employee with the right skills. As the competition for skilled workers grows, it becomes more difficult to attract and keep those workers who have the requisite training and experience.